Treating posttraumatic stress disorder using Narrative Exposure Therapy: A study of domestic violence survivors in south India - Raghuraman, Shruti (2022)
The current understanding of domestic violence is largely nomothetic by design and does not adequately address the treatment and rehabilitation needs of survivors. This thesis aimed to gain a qualitative understanding of the culture-specific experiences of domestic violence in south Indian female survivors, with a focus on the treatment of posttraumatic stress disorder (PTSD), and comorbid psychopathology. An interpretative phenomenological analysis was undertaken with five south Indian women to investigate the in-depth, lived experiences of domestic violence and its mental health sequelae. Responses to, and appraisals of abuse were found to be heavily influenced by pre-abuse identity, interpersonal childhood experiences, societal perceptions of, and stigmatising attitudes towards survivors. These factors impact the experience of disclosure and help-seeking among survivors, with a clear preference for informal sources of support such as family and social care organisations. Further, the findings shed light on the experience of resisting and counteracting the abuse in this context, as well as the complex, non-linear and iterative process of leaving abusive relationships. This was found to be rooted in the sociocultural framework of Indian society, patriarchal ideologies of gender roles, and the systemic and structural disempowerment of women, perpetuating the perpetration and experience of abuse and violence.